Ownership Concentration and Environmental, Social, Governance Engagement: Do CEO’s Characteristics Moderate the Relationship? - Ranjan DasGupta; Rajesh Pathak (Australasian Accounting, Business and Finance Journal, 2024)
In this study we examine the role of ownership concentration (OC) in determining environmental, social, governance (ESG) engagement of Indian firms. Furthermore, we evaluate the moderating role of firm’s CEO’s characteristics to attenuate or strengthen the OC and ESG linkage. This study has collected the firm level data from Centre for Monitoring Indian Economy’s (CMIE’s) Prowess Database. Its final sample consists of 161 firms for the period 2014-19, i.e., 805 firm-year observations. We have used panel fixed effect models with appropriate specifications and tests. Our results do not prove any ESG engagement due to PPC conflicts initially, however, when the firm is run by an old CEO or a busy CEO or a CEO with long tenure within a firm, ESG engagement increases. This augments agency problems in Indian firms. This is the first study to examine principal-principal conflicts from the lens of ESG performance and how CEO’s characteristics can moderate those impacts in the emerging market context of India.
Keywords: Principal-principal conflicts; ESG performance; CEO characteristics; Indian firms